2022
DOI: 10.3390/jcm11237045
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Electrode Insertion in Cochlear Implantation Controlled by Intraoperative Electrocochleography—A Pilot Study

Abstract: Robotics in otology has been developing in many directions for more than two decades. Current clinical trials focus on more accurate stapes surgery, minimally invasive access to the cochlea and less traumatic insertion of cochlear implant (CI) electrode arrays. In this study we evaluated the use of the RobOtol® (Collin, Bagneux, France) otologic robot to insert CI electrodes into the inner ear with intraoperative ECochG analysis. This prospective, pilot study included two adult patients implanted with Advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…To date, one other group has performed a similar study. Gawęcki et al (27) previously reported the use of the RobOtol robotic system (Collin, Bagneux, France) to insert AB electrodes with simultaneous intraoperative ECochG in two adult patients. At 1-month follow-up, both patients had preserved pure tone thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, one other group has performed a similar study. Gawęcki et al (27) previously reported the use of the RobOtol robotic system (Collin, Bagneux, France) to insert AB electrodes with simultaneous intraoperative ECochG in two adult patients. At 1-month follow-up, both patients had preserved pure tone thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Steady and slow insertion may also enhance feedback to the surgeon by facilitating intraoperative physiological measures of cochlear activity such as electrocochleography (ECochG). ECochG is based on electric potentials generated by the inner ear and auditory nerve in response to acoustically evoked stimulation (25)(26)(27). By using the cochlear implant electrode as a recording electrode, ECochG responses can be obtained intracochlearly and measured during insertion, informing the surgeon of potential trauma and loss of residual hearing (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first time that such remote EAI has been reported in cochlear implantation. To date, several teams has reported this type of EA-insertion using RobOtol ® but none of them used fluoroscopy as visual feedback [7,17,18]. Recently, a cochlear implantation under fluoroscopy with the HEARO procedure has been reported [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this series, we did not use intraoperative electrocochleography (EcoG). It is interesting to note that intraoperatively EcoG during a rob-EAI using the RobOtol ® has been proven feasible [18]. In order to improve the chance of hearing preservation, a rob-EAI could be advantageously associated with fluoroscopy and intraoperative EcoG monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to reduce trauma through methods such as magnetic guidance have been attempted [ 20 , 21 , 22 , 23 ], but the placement of an array inside the cochlea is not considered a safe option for patients with inner ear diseases who do not require CI for hearing rehabilitation [ 14 ]. Developing robotic platforms specified for CI-based drug delivery is still a point of interest [ 24 , 25 , 26 ]. For more details about cochlear implants, the reader can refer to [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%